Potensi Propolis dan Kombinasi Dengan Klorokuin Sebagai Antimalaria Pada Mencit (Mus Musculus) yang Terinfeksi Plasmodium berghei - Astuty, Hendri; Farhan, Muhamad; Winita, Rawina (Universitas Mohammad Husni Thamrin, 2025)
Malaria is still a public health problem both in Southeast Asia and other regions of the world. The emergence of resistance to several malaria drugs, including chloroquine. With the increase in malaria resistance, including chloroquine. With the increase in malaria drug resistance, many studies have been conducted to find new antimalarial compounds. One of them is propolis which contains luteolin 7-O glucoside which can inhibit the biosynthesis of parasitic type 2 fatty acids and chalcone can inhibit the hemolysis process. This study aims to examine the therapeutic potential of propolis single and combination with chloroquine in male Mus musculus infected with Plasmodium berghei. The single propolis tested were 30 mg/kgBW, 60 mg/kgBW and a combination of propolis. This study is an experimental laboratory study with a post-test control group-only design. Comparison of parasitemia density with the 4-day suppression test method in all treatment groups with the Kruskal-Wallis test found a p-value <0.001. The results study showed that single propolis at a dose of 30 mg/kg BW was better than a dose of 60 mg/kg BW. Combination therapy between propolis and chloroquine at doses of 30 mg/kg BB and 60 mg/kg BB had significant results. The conclusion of this study shows that combination therapy of propolis at a dose of 30 mg/kg WB or a dose of 60 mg/kg BB with chloroquine has better antimalarial potential, so propolis is synergistic with chloroquine as an antimalarial. Keywords: Propolis , Chloroquine, Plasmodium berghei, Parasitemia